2008
DOI: 10.1523/jneurosci.0979-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PINK1 Function Affects Development and Results in Neurodegeneration in Zebrafish

Abstract: Parkinson's disease (PD) is the second most prevalent neurodegenerative disorder in the Western world. PTEN (phosphatase/tensin homolog on chromosome 10)-induced putative kinase 1 (PINK1), a putative kinase that is mutated in autosomal recessive forms of PD, is also implicated in sporadic cases of the disease. Although the mutations appear to result in a loss of function, the roles of this protein and the pathways involved in PINK1 PD are poorly understood. Here, we generated a vertebrate model of PINK1 insuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(125 citation statements)
references
References 37 publications
5
116
3
1
Order By: Relevance
“…PINK1 has recently been shown to interact with and phosphorylate the embryonic ectoderm development polycomb histone-methylation modulator, redistributing it to the mitochondria, resulting in a favorable change in transcription regulation for neuronal differentiation [74]. PINK1 downregulation in zebrafish results in delayed brain development, enlarged ventricles and a moderate decrease in TH-positive neurons in the diencephalon, likely due to an increase in apoptosis as evidenced by an increase in active Caspase 3 in these embryos [75].…”
Section: Evidence For a Developmental Component Of Pd: Deregulated Emmentioning
confidence: 99%
“…PINK1 has recently been shown to interact with and phosphorylate the embryonic ectoderm development polycomb histone-methylation modulator, redistributing it to the mitochondria, resulting in a favorable change in transcription regulation for neuronal differentiation [74]. PINK1 downregulation in zebrafish results in delayed brain development, enlarged ventricles and a moderate decrease in TH-positive neurons in the diencephalon, likely due to an increase in apoptosis as evidenced by an increase in active Caspase 3 in these embryos [75].…”
Section: Evidence For a Developmental Component Of Pd: Deregulated Emmentioning
confidence: 99%
“…The loss of functional PINK1 was found to result in increased reactive oxygen species (ROS) levels, enhanced lipid peroxidation, altered glutathione metabolism, enhanced MnSOD levels, impaired glucose import, a decrease of complex I respiration, ATP production, mitochondrial membrane potential and cristae length, a deficit in mtDNA synthesis and levels, an overload of calcium, uncontrolled cytochrome C release, elevated caspase-3 activity and GSK3beta activity (Wang et al , 2007Yang et al 2006;Hoepken et al 2007;Anichtchik et al 2008;Gautier et al 2008;Piccoli et al 2008;WoodKaczmar et al 2008;Gandhi et al 2009;Grünewald et al 2009;Gegg et al 2009;Gispert et al 2009;Marongiu et al 2009). Efficient rescue of this pathology was observed with drugs such as the mitochondrial permeability transition pore blocker cyclosporin A, the mitochondrial calcium influx blocker ruthenium red and the GSK3beta inhibitor LiCl (Anichtchik et al 2008;Marongiu et al 2009). The consequences of mitochondrial dysfunction for the organism include defective axonal outgrowth observed in PINK1 deficient C. elegans (Sämann et al 2009).…”
Section: Pink1 Loss-of-function Induces Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Injection of human PINK1 mRNA with either the PD mutations A168P or W437X fails to rescue the MO phenotype. 118 These mRNA rescue experiments highlight the utility of the zebrafish model to validate homologous genes using simple micro-injection techniques, again offering an advantage over mammalian systems.…”
Section: Manipulations Of Park2 In Zebrafishmentioning
confidence: 99%
“…In zebrafish studies of PD, mitochondrial membrane potential has been tested in isolated mitochondria, 117,118 but no study of mitochondrial dynamics or mitophagy was performed prior to their isolation, and so it is suggested that further experiments may prove informative. Gross morphological analysis has been performed on mitochondria in some zebrafish models of PD, 116,117 but these did not show any abnormalities.…”
Section: Disease-induced Mitophagic Defects: Pink1 and Park2mentioning
confidence: 99%
See 1 more Smart Citation